Genome-Scale Cloning and Expression of Individual Open Reading Frames Using Topoisomerase I-Mediated Ligation - Heyman, John A.; Cornthwaite, Jeremiah; Foncerrada, Luis; Gilmore, Jeremiah R.; Gontang, Erin; Hartman, Kristen J.; Hernandez, Cathy L.; Hood, Rhiannon; Hull, Heather M.; Lee, Wai-Yee; Marcil, Robert; Marsh, Ed J.; et al. (Genome Research, 1999)
The in vitro cloning of DNA molecules traditionally uses PCR amplification or site-specific restriction endonucleases to generate linear DNA inserts with defined termini and requires DNA ligase to covalently join those inserts to vectors with the corresponding ends. We have used the properties of Vaccinia DNA topoisomerase I to develop a ligase-free technology for the covalent joining of DNA fragments to suitable plasmid vectors. This system is much more efficient than cloning methods that require ligase because the rapid DNA rejoining activity of Vaccinia topoisomerase I allows ligation in only 5 min at room temperature, whereas the enzyme’s high substrate specificity ensures a low rate of vector-alone transformants. We have used this topoisomerase I-mediated cloning technology to develop a process for accelerated cloning and expression of individual ORFs. Its suitability for genome-scale molecular cloning and expression is demonstrated in this report.